2022
DOI: 10.3390/ijms23105795
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow MSC Secretome Increases Equine Articular Chondrocyte Collagen Accumulation and Their Migratory Capacities

Abstract: Equine osteoarthritis (OA) leads to cartilage degradation with impaired animal well-being, premature cessation of sport activity, and financial losses. Mesenchymal stem cell (MSC)-based therapies are promising for cartilage repair, but face limitations inherent to the cell itself. Soluble mediators and extracellular vesicles (EVs) secreted by MSCs are the alternatives to overcome those limitations while preserving MSC restorative properties. The effect of equine bone marrow MSC secretome on equine articular ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Some studies have already demonstrated the potential of MSCderived secretome in cartilage regeneration and, consequently, their usefulness for OA therapy (Cosenza et al, 2017;Velot et al, 2021). Recently, we showed that an unstimulated BM-MSC secretome promotes collagen production in equine articular chondrocytes (eACs) and increases their migratory capacities (Contentin et al, 2022). Interestingly, intra-articular injections of the MSC secretome in an equine model of joint inflammation show anti-inflammatory effects comparable to those observed with the direct injection of MSCs (Kearney et al, 2022).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some studies have already demonstrated the potential of MSCderived secretome in cartilage regeneration and, consequently, their usefulness for OA therapy (Cosenza et al, 2017;Velot et al, 2021). Recently, we showed that an unstimulated BM-MSC secretome promotes collagen production in equine articular chondrocytes (eACs) and increases their migratory capacities (Contentin et al, 2022). Interestingly, intra-articular injections of the MSC secretome in an equine model of joint inflammation show anti-inflammatory effects comparable to those observed with the direct injection of MSCs (Kearney et al, 2022).…”
Section: Introductionmentioning
confidence: 84%
“…However, low production yields and lack of disease specificity are limitations that prevent the use of MSC secretome-based therapy to its full capacity (Chen et al, 2022). Furthermore, when eACs are cultured with the naïve MSC secretome, the neosynthesized ECM contains type I collagen, suggestive of fibrocartilage formation (Contentin et al, 2022). Because the MSC-secretome composition highly depends on the environment that the MSCs develop in, it is possible to enhance the secretion of MSCs for therapeutic applications thanks to several methods (Jammes et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies have demonstrated the therapeutic potential of eMSC-EVs in the context of horse OA. Using an in vitro cartilage organoid model, our research group has already demonstrated the pro-anabolic potential of eMSC-conditioned media (CM) and the presence of exosomes in eMSC-CM (28). The CM corresponds to the medium in which cell were cultured, hence it contains components that had been secreted by the cells.…”
Section: Mesenchymal Stromal Cell-derived Extracellular Vesicles As A...mentioning
confidence: 99%
“…It has already been proven that the unstimulated eMSC secretome can enhance the equine articular chondrocyte phenotype and increase their migratory capacity (28,30). Nevertheless, therapeutic capacities of naive MSCs developing in a healthy environment have not been optimized.…”
Section: Future Directions To Enhance the Therapeutic Potential Of Ms...mentioning
confidence: 99%
“…Gradually, EVs are considered to be the latest candidates for cartilage injury, and study has demonstrated that EVs show excellent potential in cartilage repair 13 . A mass of studies have confirmed the safety and effectiveness of EVs for the treatment of cartilage defects in small animals, although their utility in large animal models is less well established In a study based on OA in equine chondrocytes, MSCs‐EVs (less than 200 nm in diameter) were observed to be more effective than MSCs in increasing chondrocyte proliferation and migration to maintain the equine chondrocytes phenotype, suggesting that MSCs‐EVs promoted cartilage repair and delayed the progression of OA 14 . Furthermore, a study demonstrated superior outcomes using EVs combined with hyaluronic acid over hyaluronic acid alone in treating cartilage defects in micropigs, with improvements noted in MRI scores, histology, biomechanics, and bone mass.…”
Section: Introductionmentioning
confidence: 99%